Petro : Åel caudillo de los indignados? : palabras de Gustavo Petro Urrego en la Plaza de Bolâivar de Bogotâa - Petro, Gustavo (Editorial La Oveja Negra Ltda., 2014)
Consists primarily of addresses delivered by Petro as Alcalde Mayor of Bogotâa between December 9, 2013, and January 13, 2014, in part regarding an attempt by the Procuradurâia General of Colombia to remove him from office.